Automatyczna analiza morfologiczna jako narzedzie oceny poprawnosci wyrazów jezyka rosyjskiego - Fiedoruszkow, Jurij (Investigationes Linguisticae, 2005)
Processes of lemmatizing are beginning to play a very important role in contemporary linguistic methods. A lemmatizer as an instrument in computer analysis morphologically analizes texts and corpuses of texts and at the same time functions as a program module and a lemmatizing algorithm. The identification of lexemes depends on the organization of the dictionary data. One of the examples of the practical results of lemmatization is the set of unrecognized words (with a precise determination of the membership of morphological markers and parts of speech) in a language. In this paper, the methodological description of the use of the program Lemmatizer with the use of an electronic text (as an example) in Russian is proposed.